Agribusiness-Based Corn Crop Development Strategy - Crisdayanti, Crisdayanti; Yusriadi, Yusriadi; Nurhaedah, Nurhaedah (LaGeografia, 2021)
This study aims to identify internal and external factors in the development of agribusiness-based corn plants and determine alternative strategies for agribusiness-based corn plant development in Pattondonsalu Village, Maiwa District, Enrekang Regency. The population in this study were 252 people. The method of random sampling for corn farmers was 21 people and the determination of key informants was deliberately taken (puposive) as 4 people because they were considered to know the most about the information presented, making it easier for the research process. The method used in this research is descriptive qualitative. This study uses IFAS, EFAS, and SWOT matrix data analysis. The research results are based on the analysis of the SWOT matrix, the appropriate alternative strategy is the Strategy-Oppottunities Strategy which is obtained from internal strength factors and external opportunities, namely Utilizing the availability of agricultural land to carry out corn cultivation activities so that the amount of corn demand can be met by utilizing technology and availability of facilities. superior and quality production by working with supporting institutions and input production retailers to meet the needs of farming and working with members of farmer groups to increase farmer motivation and absorption of labor from farmer groups so that maximum profits can be obtained.